2010
DOI: 10.1042/cs20100280
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) infusion is associated with increased blood pressure and adverse cardiac remodelling in rats with subtotal nephrectomy

Abstract: ACE (angiotensin-converting enzyme) 2 is expressed in the heart and kidney and metabolizes Ang (angiotensin) II to Ang-(1–7) a peptide that acts via the Ang-(1–7) or mas receptor. The aim of the present study was to assess the effect of Ang-(1–7) on blood pressure and cardiac remodelling in a rat model of renal mass ablation. Male SD (Sprague–Dawley) rats underwent STNx (subtotal nephrectomy) and were treated for 10 days with vehicle, the ACE inhibitor ramipril (oral 1 mg·kg−1 of body weight·day−1) or Ang-(1–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 49 publications
6
92
0
4
Order By: Relevance
“…Tikellis et al described that ACE2 knockout mice exhibit an increased albuminuria in a streptozotocin-induced diabetes model, but at the same time an attenuated expression of marker genes for diabetic nephropathy. Moreover, Velkoska et al (2011) reported that Ang-(1-7) treatment of male SpragueDawley rats after subtotal nephrectomy induced deleterious cardiovascular effects as well as increasing levels of fibrosis when compared with controls. By contrast, no aggravation of renal injury produced by kidney ischemia-reperfusion was observed in Mas K/K mice, and in the same model the Mas agonist AVE 0991 reduced renal injury (Barroso et al 2012).…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Tikellis et al described that ACE2 knockout mice exhibit an increased albuminuria in a streptozotocin-induced diabetes model, but at the same time an attenuated expression of marker genes for diabetic nephropathy. Moreover, Velkoska et al (2011) reported that Ang-(1-7) treatment of male SpragueDawley rats after subtotal nephrectomy induced deleterious cardiovascular effects as well as increasing levels of fibrosis when compared with controls. By contrast, no aggravation of renal injury produced by kidney ischemia-reperfusion was observed in Mas K/K mice, and in the same model the Mas agonist AVE 0991 reduced renal injury (Barroso et al 2012).…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
“…Besides its physiological relevance for kidney homeostasis, the ACE2/Ang-(1-7)/Mas axis also has an important and controversial role in renal diseases, acting as a renoprotective (Oudit et al 2006, 2010, Soler et al 2007, Pinheiro et al 2009, Burns et al 2010, Dilauro et al 2010, Zhang et al 2010, Giani et al 2011, Liu et al 2011b, Moon et al 2011, Stegbauer et al 2011, Zhong et al 2011, Barroso et al 2012, Kim et al 2012, Nadarajah et al 2012 or a proinflammatory (Esteban et al 2009, Velkoska et al 2011 agent. Briefly, Pinheiro et al (2009) reported that mice with genetic deletion of Mas developed renal dysfunction with an increase of glomerular tuft diameter and enhancement of fibronectin and collagen IV and III deposition, besides an increase of AT 1 and TGF-b expression.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%
“…For ACE2 activity, 100 µg of protein was incubated in duplicate with an ACE2-specific quenched fluorescent substrate (QFS) (7-methoxycoumarin-4-yl)-acetyl-Ala-ProLys (2,4-dinitrophenyl) (Auspep, Victoria, Australia), 10 µM Z-Pro-prolinal (Auspep, Victoria, Australia), with or without 100 µM EDTA in a total volume of 200 µl. [12][13][14] Reactions proceeded at 37°C for 200 min with continuous monitoring of liberated fluorescence (λex = 320 nm, λex = 405 nm) using a FLUOstar Optima plate reader (BMG Labtechnologies, Offenburg, Germany). The rate of substrate cleavage was determined by comparison with a standard curve of the free fluorophore MCA (4-amino-methoxycoumarin; Sigma) and is expressed as nmol of substrate cleaved/mg of protein/h.…”
Section: Ace and Ace2 Activitymentioning
confidence: 99%
“…Blood samples for measurement of ANG II were collected into tubes containing 20 l/ml of blood of an inhibitor cocktail (50 mM EDTA, 0.2 M N-ethylmaleimide, and 1-2 trypsin inhibitory units/ml aprotinin made up in saline), and plasma was snap frozen and stored at Ϫ80°C. The radioimmunoassay for ANG II has been previously described (55,56). The anti-rabbit antibody and the specific radioisotope ( 125 I-labeled ANG II) were made by Prosearch.…”
Section: Animal Surgeries and Cardiovascular Assessmentmentioning
confidence: 99%